Disbursement management subsystem a University of the Philippines Mindanao Integrated Information Management System Module - Bonghanoy, Julius Mattheus Regual (2008)
The system is Java application that automates the processing of disbursement vouchers in the University of the Philippines Mindanao. The system is meant to be used by the different offices and departments of the university that are involved in the processing of disbursement vouchers. The system automates the process of requesting a disbursement voucher, checking the completeness of the documents, and approving the disbursement voucher. It has a user-friendly interface. The system is a part of the University of the Philippines Mindanao Integrated Information Management System (UPMIIMS) which is composed of different subsystem that are connected to a centralized database. The system?s main purpose is to make the processing of the disbursement voucher faster and easier